E-Module Mata Pelajaran Kewarganegaraan untuk Meningkatkan Hasil Belajar Siswa - Dian Arief Pradana; Sihkabuden; Arafah Husna (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
This development aims to produce class X Citizenship learning e-module products that can be used as an attractive and effective learning medium. Arief S. Sadiman's (2011) model was used in this development. The result of this development is in the form of an e-module for the Citizenship subject in the competency standard "Analyzing the Political System in Indonesia". The product is validated by media experts, material experts and user students, and declared valid or suitable for use as a learning medium.